2019
DOI: 10.3390/w11040732
|View full text |Cite
|
Sign up to set email alerts
|

Insecure Security: Emergency Water Supply and Minimum Standards in Countries with a High Supply Reliability

Abstract: Drinking water supply is at the core of both, humanitarian action in times of crisis, as well as national policies for regular and emergency supply. In countries with a continuous water supply, the population mostly relies ingenuously on the permanent availability of tap water due to high supply standards. In case of a disruption in the drinking water infrastructure, minimum supply standards become important for emergency management during disasters. However, wider recognition of this issue is still lacking, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 28 publications
(35 reference statements)
0
22
0
Order By: Relevance
“…Water moves from the feed (low salt concentration) to the draw solution (high salt concentration) [95]. There have been many multifarious studies conducted on FO applications, for instance, minimizing the leachate from sanitary landfills [95], reducing salt content in draw solutions [95][96][97][98], identification of fruit juice concentrations [95], provision of emergency water supply [99], reducing RO [100] and anaerobic digester concentrate [101], volume production, and lastly, treatment of wastewater with high salt content in petrochemical and fracking industries [101,102]. A study conducted by Wang and Ng employed draw solution containing 5-6 M of fructose and treated reverse osmosis concentrates (ROC) consisting approximately 1.5 M of NaCl-passing through a FO membrane with a cellulose acetate matrix [100].…”
Section: Forward Osmosismentioning
confidence: 99%
“…Water moves from the feed (low salt concentration) to the draw solution (high salt concentration) [95]. There have been many multifarious studies conducted on FO applications, for instance, minimizing the leachate from sanitary landfills [95], reducing salt content in draw solutions [95][96][97][98], identification of fruit juice concentrations [95], provision of emergency water supply [99], reducing RO [100] and anaerobic digester concentrate [101], volume production, and lastly, treatment of wastewater with high salt content in petrochemical and fracking industries [101,102]. A study conducted by Wang and Ng employed draw solution containing 5-6 M of fructose and treated reverse osmosis concentrates (ROC) consisting approximately 1.5 M of NaCl-passing through a FO membrane with a cellulose acetate matrix [100].…”
Section: Forward Osmosismentioning
confidence: 99%
“…In case of an emergency, it is necessary to limit damages to critical infrastructures and to prevent possible corresponding disruptions of services (Wannous and Velasquez 2017). This objective is particularly relevant due to new security policy risks like international terrorism and significant natural risks that have an enhanced potential to damage critical infrastructures (Bross et al 2019). Therefore, authorities need to update their continuity plans regularly and make sure that each part of the critical infrastructure is protected.…”
Section: Motivationmentioning
confidence: 99%
“…For example, an earthquake caused significant disturbance of the water system in Los Angeles in 1994 (Davis 2014), a long-lasting drought put the supply in Kapstadt under heavy pressure (Enqvist and Ziervogel 2019). Moreover, severe flooding led to a collapse of the water distribution of Gloucestershire (Rundblad et al 2010) and Simbach am Inn in Germany (Bross et al 2019). While a lot of measures and contingencies are in place to repair and reestablish water supply, it is important to develop plans to mitigate the consequences of a disruption.…”
Section: Motivationmentioning
confidence: 99%
“…According to some studies, the outbreak of a post-seismic fire has the most devastating effects [4,8]. In the earthquake of 1906 in San Francisco, USA-known as the biggest urban disaster produced in peacetime-to the one that occurred in Asia in 2006, damage to water distribution pipelines has impeded interventions to extinguish the fire, with consequent human and material damage being major: 3000 dead persons and the destruction of 28,000 buildings.…”
Section: Current State Of Researchmentioning
confidence: 99%
“…Practice has revealed that adductions and distribution networks are the most vulnerable to seismic action [4]. Their sensitivity to this type of action, even if of low intensity, is caused by the fact that they are carried out over extended areas, with large variability in the physical-mechanical features of the land in which they are located.…”
Section: Introductionmentioning
confidence: 99%